THE AUDIT BOARD OF REPUBLIC OF INDONESIA OPINION AND BRIBERY IN LOCAL GOVERNMENTS IN INDONESIA - Astuti, Yuniasih Dwi; Adrison, Vid (Badan Pemeriksa Keuangan Republik Indonesia, 2019)
This study is motivated by the trend of corruption cases which increase from year to year, where bribery is the first number in corruption cases. As many as 128 cases of bribery with in kracht status occurred in the local government that received an unqualified opinion from the Audit Board of the Republic of Indonesia (BPK RI). Using the Zero Inflated Poisson (ZIP) Panel Regression, this study examines the correlation between financial statement opinion and the number of bribery corruption cases based on 258 bribery cases that have been handled by the Corruption Eradication Commission (KPK) in the period 2008-2017. The estimation result shows that there was no correlation between financial statement opinion and the number of bribery cases. However, the increase in the amount of capital expenditure also goods and services expenditure is related to the increase in the number of bribery cases. This study recommends BPK to consider improving the quality of fraud detection through audit procedures on financial statements, especially in regions that have a relatively high value of capital expenditure and service goods expenditure.